2019
DOI: 10.1016/j.jmmm.2019.04.076
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of nanoparticle heating and amoxicillin on H. pylori inhibition

Abstract: We report the design and development of a dual-functional magnetic nanoparticle platform for potential treatment of H. pylori infection. We show that an ultralow concentration of Mn0.3Fe2.7O4@SiO2 nanoparticles subjected to a moderate AC magnetic field, without bulk heating effect, can deposit heat locally and effectively inhibit H. pylori growth and virulence in vitro. When coupled with antibiotic amoxicillin, the dual-functional amoxicillin loaded Mn0.3Fe2.7O4@SiO2 further decreases the bacteria survival rat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Thermal shock has been demonstrated as a means of deactivating established biofilms but may also damage adjacent tissue [ 33 , 34 ]. Recent studies have suggested a synergism between antibiotics and thermal shock, with the combined treatment decreasing biofilm population density more than either treatment alone, or even by the product of their individual effects [ 35 , 36 , 37 , 38 ]. The nature of this interaction is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal shock has been demonstrated as a means of deactivating established biofilms but may also damage adjacent tissue [ 33 , 34 ]. Recent studies have suggested a synergism between antibiotics and thermal shock, with the combined treatment decreasing biofilm population density more than either treatment alone, or even by the product of their individual effects [ 35 , 36 , 37 , 38 ]. The nature of this interaction is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Pijls et al [32] investigated the synergistic effects of non-contact induction heating and antibiotic cocktails and reported that a combination of heat plus antibiotics had synergistic effects on Staphylococcus aureus biofilms at 60 C. Both studies achieved promising results; however; they performed their research at high temperatures, which may cause thermal damage to human tissue. Wu et al [33] designed a magnetic nanoparticle platform to investigate the synergistic effects of nanoparticle heating and the antimicrobial drug amoxicillin on H. pylori and reported that this combination increased the susceptibility of H. pylori to amoxicillin due to the destruction of the cell membrane and microbial biofilm at 41 C. In contrast to our study, they used amoxicillin-loaded nanoparticles in their research. In 2020, Alumutairi et al [34] reported that magnetic nanoparticle hyperthermia enhanced the susceptibility of S. aureus biofilm to ciprofloxacin and vancomycin antibiotics.…”
Section: Colony Counts At 1st Hourmentioning
confidence: 69%
“…Alteration of antimicrobial susceptibility was reported after hyperthermia on Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, and our previous study found that NPs magnetic local heating could not only disrupt H. pylori cell directly, but could also enhance its susceptibility to amoxicillin, of which could be adopted for clinic applications readily [44][45][46][47][48]. One crucial mechanism of drug resistance is the formation of bio lms.…”
Section: Discussionmentioning
confidence: 99%